La nouvelle convention sur le droit de la mer et la lutte contre la pollution marine d'origine tellurique - Taschereau, Louis (Les Cahiers de droit, 1983)
Several articles of the Charter of the Law of the Sea deal with land-based pollution, which is responsible for approximately 90% of all high sea's pollution. A detailed study of these articles shows that the Charter under-emphasizes the importance of land-based pollution. Authority to solve marine pollution is left to coastal states, who are but vaguely obliged to encourage means of regional cooperation to curtail damage to marine environment. These obligations are a first step in the long and difficult process of bringing about efficient pollution control by way of international cooperation.